(untitled) (Praxis Educativa, 2022)
This article presents the outcomes of a qualitative study about “Todos ABC Monseñor Leonidas Proaño (phase 1)” campaign, the objective was to determine the discourses on the adult literacy process. The methodological proposal emerged from narrative research as a route for the construction of knowledge. As a result, three life histories of students -between September 2017 to October 2019- from different regions of Ecuador were analyzed. The outcomes refer to the dissonance of circumscribed discourses throughout the participants’ lives, which tend to maintain or promote an order in relation to literacy. Therefore, it is concluded that adult education requires pedagogical strategies focused on biographical methods to promote significant and sustained learning over time. Finally, the article proposes certain recommendations for the design of educational policies concerning adult education.